Comparison of reference signal extraction methods for active power filter to mitigate load harmonics from wind turbine generator - Qazi, S. H. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper highlighting on two reference extraction methods; Synchronous Reference Frame (SRF) and Instantaneous Reactive Power Theory. The operation of these two techniques will be analyzed with variable speed grid connected permanent magnet synchronous generator based wind turbine system. The simulated results will confirm which method has better performance and which can maintain total harmonic distortion THD level of the system at the value specified by IEEE standard 519 when applied with wind energy conversion system.